Step1:
(iii)Given:-
$A=\begin{bmatrix}0 & -1 & 2\\4 & 3 & -4\end{bmatrix}$
LHS:-
$KA=K\begin{bmatrix}0 & -1 & 2\\4 & 3 & -4\end{bmatrix}$
$(KA)=\begin{bmatrix}0 &-K&2K\\4K & 3K&-4K\end{bmatrix}$
$(KA)'=\begin{bmatrix}0 &4K\\-K&3K \\ 2K&-4K\end{bmatrix}$
Step2:
RHS:-
$A=\begin{bmatrix}0 & -1 & 2\\4 & 3 & -4\end{bmatrix}$
$A'=\begin{bmatrix}0 & 4 \\-1 & 3 \\2& -4\end{bmatrix}$
$(KA')=K\begin{bmatrix}0 & 4 \\-1 & 3 \\2& -4\end{bmatrix}$
$\;\;\;=\begin{bmatrix}0 & 4K \\-K & 3K \\2K& -4K\end{bmatrix}$
$\Rightarrow LHS=RHS.$
$\Rightarrow (KA)'=(KA')$